Controlled longitudinal study of bone mass accrual in children and adolescents with cystic fibrosis. Issue 2 (29th December 2005) - Buntain, H M; Schluter, P J; Bell, S C; Greer, R M; Wong, J C H; Batch, J; Lewindon, P; Wainwright, C E
Abstract : Background: A study was undertaken to observe the gains in bone mass in children and adolescents with cystic fibrosis (CF) over 24 months and to examine the relationship between areal bone mineral density (aBMD) and associated clinical parameters including physical activity, nutrition, and 25-hydroxyvitamin D (25OHD). Methods: Areal BMD of the total body (TB), lumbar spine (LS), and total femoral neck (FNt) were repeatedly measured in 85 subjects aged 5–18 years with CF and 100 age and sex matched controls over 2 years. At each visit anthropometric variables, nutritional parameters, pubertal status, disease severity, physical activity, dietary calcium, caloric intake, and serum 25OHD were assessed and related to aBMD. Results: After adjusting for age, sex, and height Z-score, gains in LS aBMD in children (5–10 years) and TB and FNt aBMD in adolescents (11–18 years) with CF were significantly less than in controls. Lean tissue mass was significantly associated with TB and LS aBMD gains in children and adolescents and explained a significant proportion of the aBMD deficit observed. Lung function parameters were significantly associated with aBMD gains in adolescents with CF. Conclusions: Inadequate bone mass accrual during childhood and adolescence contributes to the low bone mass observed in adults with CF. Accounting for the height discrepancy which is frequently observed in those with CF, in addition to age and sex, is important when assessing low bone mass in children and adolescents with CF. To optimise an individual's potential to acquire maximal bone mass, it is necessary to maximise nutritional status and limit the progression of chronic suppurative lung disease.